Louis I. Kahn towards the zero degree of concrete ; 1960-1974 - Rosellini, Anna 1977- (Treatise on concrete, 2014)
Through sheer determination and courage, Kahn has researched the nature of concrete in the form of precast, cast in place or blocks. Each of his renowned works in exposed concrete, such as the Yale Art Gallery, the Richards Laboratories, the Bath House, the Salk Institute, the National Assembly, the Kimbell Museum, the Exeter Library and the Yale Center for British Art, is itself an important chapter in the history of architecture for the exploration into concrete' s formal expression, beyond the lessons of Le Corbusier.Kahn' s obsessionwith concrete'